Nontrivial solutions for nonvariational quasilinear neumann problems - Papageorgiou, Nikolaos S. (2012)
We consider a nonlinear nonvariational Neumann problem with a nonsmooth potential. Using the spectrum of the assymptotic (as |x| - ∞) differential operator and degree theoretic techniques based on the degree map of certain multivalued perturbations of (S)+-operators, we establish the existence of at least one nontrivial smooth solution.